The Curious Case of Construction of Quality in Nordic Business Schools – The Symbolic Role of Branding - Kallio, Tomi J.; Kallio, Kirsi-Mari; Suomi, Kati; Funck, Elin K. (University of Gothenburg, 2026)
Universities worldwide have increased their competition for the best students and employees. Consequently, business schools are pressured to demonstrate excellence and differentiate themselves through brand building. One essential part of branding is the quality narratives that universities present to the public. We study the presentation of quality in Nordic business schools. Data concerning the presentation and manifestation of quality by the Nordic business schools was collected from 41 business schools’ public web pages. We used content analysis to gather 12 quality narratives and interpret them. We identify 12 items applied in the quality narratives by the studied business schools. Our results show homogeneity in communication stemming from the pursuit of legitimacy and conformity to expectations. We demonstrate that the visible manifest content of the quality manifestos of Nordic universities functions as artifacts similar to tangible and visual representations, heavily laden with market-oriented neoliberal values. We highlight how Nordic business schools have predominantly adopted a uniform approach to branding in higher education, as the universities align with their institutional settings.